Партизанський рух у Південній Україні у 1943–1944 рр. - Слободянюк, Микола Анатолійович (Дніпровський національний університет імені Олеся Гончара , Дніпро, 2017)
UKR: Стаття присвячена завершальному етапу (1943–1944 рр.) розвитку радянського партизанського руху в Південній Україні. Цей регіон відрізняється відсутністю великих лісових масивів та наявністю великих промислових центрів. З огляду на це, пріоритетними там стали підпільні форми боротьби. Тим не менше, партизанські методи спротиву окупантам також доволі активно використовувалися. На основі аналізу широкого кола архівних документів центральних і обласних архівосховищ встановлено, що за своїми характеристиками завершальний етап розвитку партизанського руху суттєво відрізнявся від етапу початкового (1941–1942 рр.). Його особливостями стали відмінний механізм виникнення партизанських формувань, видозмінена тактика боротьби з окупантами. Зокрема, у 1943–1944 рр. партизанські загони формувалися внаслідок організаторської діяльності десантних груп, закинутих з «Великої землі», або підпільниками. З’ясовано, що активну діяльність вони розгортали при наближенні лінії фронту: нападали на окупаційні підрозділи та установи, здійснювали диверсійні акти, вели розвідку в інтересах Червоної армії. Видатною сторінкою руху Опору на півдні України стало Павлоградське повстання 1943 року. Загалом партизанський рух у Південній Україні зробив помітний внесок у вигнання нацистських окупантів з української землі.

RUS: Статья посвящена завершающему этапу (1943–1944 гг.) Развития советского партизанского движения в Южной Украине. Этот регион отличается отсутствием крупных лесных массивов и наличием крупных промышленных центров. Учитывая это, приоритетными там стали подпольные формы борьбы. Тем не менее, партизанские методы сопротивления оккупантам также довольно активно использовались. На основе анализа широкого круга архивных документов центральных и областных архивохранилищ установлено, что по своим характеристикам завершающий этап развития партизанского движения существенно отличался от этапа начального (1941–1942 гг.). Его особенностями стали отличный механизм возникновения партизанских формирований, видоизмененная тактика борьбы с оккупантами. В частности, в 1943–1944 гг. партизанские отряды формировались в результате организаторской деятельности десантных групп, заброшенных с «Большой земли», или подпольщиками. Выяснено, что активную деятельность они разворачивали при приближении линии фронта: нападали на оккупационные войска и учреждения, осуществляли диверсионные акты, вели разведку в интересах Красной армии. Выдающейся страницей движения Сопротивления на юге Украины стало Павлоградское восстание 1943 года. В общем, партизанское движение в Южной Украине внес заметный вклад в изгнание нацистских оккупантов с украинской земли.

ENG: The events of the Revolution of Dignity and war in Donbass formed the experience of the armed and sociopolitical con- frontation of the Second World War period, especially in the steppe and industrial south of Ukraine. Partisan struggle in this region had its own specifics, which requires its comprehension and generalization. The article is devoted to the final stage (1943–1944) of the development of the Soviet partisan movement in Southern Ukraine. This region is characterized by the absence of large forest areas and the presence of large industrial centers. Considering this, underground forms of struggle became the priority ones. Nevertheless, partisan methods of resistance to the invaders were also used actively. Based on the analysis of a wide range of archival documents of the central and regional archives, it has been established that the final stage of development of the partisan movement in its characteristics differed significantly from the initial stage (1941–1942). Its features were: the excellent emergence of partisan formations and a modified tactic of fighting against the invaders. In particular this happened in years 1943–1944. Partisan detachments were formed as a result of the organizational activities of the landing groups, abandoned from «Big Land» or underground. It has been found out during the investigation that they were active in the approaching front line: they attacked the occupation troops and institutions, carried out diversionary acts, conducted reconnaissance in the interests of the Red Army. An outstanding page of the Resistance movement in the south of Ukraine was Pavlograd uprising of 1943. In addition, the quality of the source base has been described in the article. It has been established that the documents of the Soviet archives contain a considerable part of falsifications and exaggerations. Therefore, researchers are being recommended to use the quantitative indicators of Soviet documents very critically and only as approximate, which reflect certain phenomena and general trends, and which are not absolutely reliable facts. In general, the partisan movement in South Ukraine made a significant contribution to the expulsion of the Nazi occupiers from the Ukrainian land. It raised the morale of the local population, disarmed the invaders, distracted the significant military units of the enemy.
Партизанское движение в Южной Украине в 1943-1944 гг.
Partisan Movement in Southern Ukraine in 1943–1944.
М. Слободянюк: ORCID: 0000-0003-2218-0818
Keywords: партизанський рух; підпілля; історіографія; Південна Україна; окупація; ефективність; партизанское движение; подполье; историография; Южная Украина; оккупация; эффективность; partisan movement; underground; historiography; Southern Ukraine; occupation; efficiency; КУГПІС